Characterizing Industrial VOC Hotspots in One of Eastern China’s Largest Petrochemical Parks Using Mobile PTR–ToF–MS Measurements - Jie Fang; Zihang Zhang; Zeye Liang; Ming Wang; Yunjiang Zhang; Xinlei Ge (Atmosphere)
The industrial emissions of volatile organic compounds (VOCs) are a major contributor to air pollution in urban areas. Previous studies on VOC emissions in industrial zones have primarily relied on in situ monitoring techniques, which pose significant challenges in capturing high emissions peaks and near-source measurements on regional scales. In this study, we employed mobile proton transfer reaction–time-of-flight–mass spectrometry (PTR–ToF–MS) to identify and characterize industrial VOC hotspots in a petrochemical park in eastern China, from June to September 2021. The average total VOC concentrations in the industrial zone were 131.5 ± 227.7 ppbv, approximately 48% higher than those in the background area (88.9 ± 63.3 ppbv), reflecting the substantial emissions from industrial hotspots. Oxygenated VOCs were the most abundant components in the industrial zone (83.2 ppbv). The overall OH reactivity, aerosol formation potential, and lifetime cancer risk of the industrial zone were also substantially higher than those in the background zone. These findings emphasize the need for targeted VOC emissions controls in industrial hotspots to mitigate air quality and health risks.